A Review of Prolate Spheroidal Wave Functions from the Perspective of Spectral Methods (Journal of Mathematical Study, 2017)
This paper is devoted to a review of the prolate spheroidal wave functions(PSWFs) and their variants from the viewpoint of spectral ⁄ spectral-element approximationsusing such functions as basis functions. We demonstrate the pros and consover their polynomial counterparts, and put the emphasis on the construction of essentialbuilding blocks for efficient spectral algorithms.